Design and Performance Evaluation of a Commercial size Fixed Dome Biogas Plant - Hakimuddin, Hakimuddin; Kurchania, A K; Mathur, Ravi; Sharma, Deepak; Ali, Nafisa (Journal of Agricultural Engineering, 2010)
A community size fixed dome cattle dung feed biogas plant of 25 m3 capacity, based on solid-state fermentation, was designed and constructed with brick masonry without using RCC. The shape of the designed plant was of capsule structure. The diameter of lower spherical segment of digester was 4.95 m with the height of the middle cylindrical section as 1.98 m and the depth of bottom spherical segment as 0.98 m. Two cement pipes, diameter 600 mm, were attached to facilitate the feeding of charge. Feeding was carried out with fresh cattle dung having moisture content of 16 per cent. The gas yield varied between 19.56 and 22.45 m3/day with methane content varying between 56.2 to 61.8 per cent. The biogas was used for operating a spark plug assisted CI engine genset to generate electricity, and also for thermal application. The brake thermal efficiency was highest (24.51%) at 4 kW load. Specific biogas consumption was highest (2.81 m3/kW.h) at 1 kW power, and least (0.8 m3/kW.h) at 4 kW.h. Pay back period was found as 4 year 1 month, with cost-benefit ratio of 2.35 for multi-purpose applications.